1992
DOI: 10.3109/10408449209145319
|View full text |Cite
|
Sign up to set email alerts
|

The Human Hepatic Cytochromes P450 Involved in Drug Metabolism

Abstract: The cytochromes P450 are a superfamily of hemoproteins that catalyze the metabolism of a large number of xenobiotics and endobiotics. The type and amount (i.e., the animal's phenotype) of the P450s expressed by the animal, primarily in the liver, thus determine the metabolic response of the animal to a chemical challenge. A majority of the characterized P450s involved in hepatic drug metabolism have been identified in experimental animals. However, recently at least 12 human drug-metabolizing P450s have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
432
0
18

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 821 publications
(453 citation statements)
references
References 134 publications
3
432
0
18
Order By: Relevance
“…A number of environmental chemicals and pollutants, including the polycyclic hydrocarbons present in cigarette smoke, are known to be potent inducers of liver enzymes [14]. These substances are capable of altering the activity of selected human cytochrome P450 isoenzymes, which are responsible for the breakdown and excretion of ingested or inhaled chemicals and toxins [15]. These reactions involve the conversion of metabolites from a hydrophobic form into a more readily excretable hydrophilic form.…”
Section: Discussionmentioning
confidence: 99%
“…A number of environmental chemicals and pollutants, including the polycyclic hydrocarbons present in cigarette smoke, are known to be potent inducers of liver enzymes [14]. These substances are capable of altering the activity of selected human cytochrome P450 isoenzymes, which are responsible for the breakdown and excretion of ingested or inhaled chemicals and toxins [15]. These reactions involve the conversion of metabolites from a hydrophobic form into a more readily excretable hydrophilic form.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with hepatic P450s have shown that P450-catalysed drug metabolism and the regulation of the expression of these xenobiotic-metabolizing enzymes can sometimes be quite different in humans compared with that found in experimental animals (Guengerich, 1989;Wrighton and Stevens, 1992;Nelson et al, 1996). In some cases, different strains within the same species may show differences in the levels of expression of specific P450s (Kraner et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…At present. the existence of human CYP forms orthologous to constitutive rat CYPs has not been established except in cases such as CYP2E1 and CYP3A subfamiiy forms (Wrighton and Stevens, 1992). Thus extrapolation of regulatory mechanisrns frorn rat to human may not always b8 possible, but in cases where rat and human orthologues clearly exist (GYP1 A1 and CYP2E1 ), mechanisms of CYP regulation appear to be conserved.…”
Section: Regulation Of Hepatic Microsomal Cypmentioning
confidence: 99%